Analisis Pertumbuhan Fintech Syariah dalam Mendorong Industri Keuangan Syariah di Indonesia - Pandu Dewanata; Rizqina Martina (PT Wacana Publisher Utama, 2026)
Indonesia's Islamic financial industry continues to expand, yet Islamic fintech's contribution to that growth remains fragmented across separate strands of literature. This study analyzes the growth pattern of Islamic fintech in Indonesia and its contribution to the development of the national Islamic financial industry. The study applies a descriptive qualitative library research method, synthesizing 43 secondary sources consisting of Sinta-indexed journal articles published within the last five years, reference books published within the last ten years, and official statistical reports from the Financial Services Authority (OJK) and the National Committee for Islamic Economy and Finance (KNEKS). The results show that Islamic fintech drives Islamic financial industry growth mainly through expanded MSME financing access, although annual asset growth slowed from 19.52 percent in 2023 to 8.56 percent in 2025, and the Islamic capital market still dominates 86 percent of total sharia financial assets, leaving banking and non-bank sharia financial institutions comparatively underdeveloped.